59.1k views
1 vote
If f(x) = 2x - 6 and g(x) = 3x + 9, find (f - g)(x).

O A. (f- g)(x) = x+15
O B. (f- g)(x) = -x+3
OC. (f- g)(x) = -x - 15
O D. (f- g)(x) = 5x + 3

User Simas
by
5.3k points

2 Answers

5 votes


(f-g)(x)=2x-6-(3x+9)=2x-6-3x-9=-x-15

User YenForYang
by
4.9k points
6 votes

Answer:

The correct option is C.

Explanation:

The correct option is C.

We have given:

f(x) = 2x - 6 and g(x) = 3x + 9

Now we have to find (f-g)(x)

(f-g)(x) = f(x)- g(x)

Now subtract g(x) from f(x)

(2x - 6) - (3x + 9)

Open the parenthesis. When we open the parenthesis the signs of second bracket will become negative because there is a negative sign outside the bracket.

(f-g)(x)= 2x-6-3x-9

Now solve the like terms:

(f-g)(x)= -x-15

Thus the correct option is C....

User David Resnick
by
6.0k points